MOTIVATION OF FISH FARMERS TO BUSINESS FLOATING CAGES IN MANINJAU LAKES BAYUR VILLAGE TANJUNG RAYA SUB-DISTRICT AGAM REGENCY WEST SUMATERA PROVINCE - Agus Rahman Ibrahim; Firman Nugroho; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The aim of these resesrch were characteristics of fish farmers, motivation of cultivator, and corelation of characteristics wich motivation to try fish farmers floating net cages. The research was conducted in march, 2018. The method use in this reaserch with survey method. The respondens taken in this reasearch was 30 people, this research shows the carakteristics of fish farmers, age on produktive categories, education in the medium category, capital in the low category, income in the high category, number of dependents in low category, high category busness experience, the number of working hours is high category. Overall fish farmers motivation is high and charakteristik with motivation show a significant effect on income, capital, number of hours worked, and the eexsperience of busines relates to the opposite. Meaning that income and capital have a correlation with the motivation to try fish farmer. Keyword’s : Motivation, Floating Net Cages, Maninjau